Healing Songs and Music in Southern Italy: the Case of Tarantism - Tita, Michele (Tautosakos darbai, 2020)
Humans have always expressed themselves through songs and it is possible to witness practices of traditional singing almost everywhere and every time. The case that I am presenting in this article refers to the context of Southern Eastern Italy until the 1960s and the practice of singing and playing instruments as a form of healing towards people affected by tarantism, a peculiar culture-bound syndrome of that geographical area nowadays extinct. Tarantism takes its name from the spider called tarantula, which was said to sting mostly women around the end of June. Music and songs belonging to the traditional and wider genre of pizzica were used to treat them. Indeed, they could get rid of the venom of the spider by dancing with this music and these songs (even though the definitive healing could have been obtained only by the grace of Saint Paul). Pizzica is still sung, played and danced in Salento nowadays, although without its original healing function. The aim of this article is, therefore, to explore some examples of pizzica as witnessed from ethnomusicologists and played nowadays, highlighting their social and cultural role in both healing and recreational contexts.